Optimizing the Minimum Cash Balance in Supporting the Company's Operational Efficiency - Venny Maulidah (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study analyzes the importance of optimal minimum cash balance management in encouraging operational efficiency, especially in the manufacturing industry in Indonesia. In this context, strategic cash management becomes vital to maintain a balance between liquidity availability and cost efficiency. The research was conducted using a quantitative approach using secondary data from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2018–2022. Multiple linear regression analysis techniques were applied to evaluate the effect of the minimum cash balance on the operating efficiency ratio, which was calculated based on the ratio between operating expenses and revenues. The results show that optimally managed minimum cash balances have a significant impact on improving operational efficiency. This reflects that companies with structured cash policies tend to be more effective in utilizing resources and avoiding idle funds. This study presents practical insights for financial decision-makers in formulating cash policies that are aligned between liquidity and efficiency needs. In addition, this research opens up opportunities for the development of a cash management framework that is responsive to industry characteristics.